Volume nucleation rates for homogeneous freezing in supercooled water microdroplets: results from a combined experimental and modelling approach - M. E. Earle; T. Kuhn; A. F. Khalizov; J. J. Sloan (Atmospheric Chemistry and Physics, 2010)
Temperature-dependent volume nucleation rate coefficients for supercooled water droplets, JV(T), are derived from infrared extinction measurements in a cryogenic laminar aerosol flow tube using a microphysical model. The model inverts water and ice aerosol size distributions retrieved from experimental extinction spectra by considering the evolution of a measured initial droplet distribution via homogeneous nucleation and the exchange of vapour-phase water along a well-defined temperature profile. Experiment and model results are reported for supercooled water droplets with mean radii of 1.0, 1.7, and 2.9 μm. Values of mass accommodation coefficients for evaporation of water droplets and vapour deposition on ice particles are also determined from the model simulations. The coefficient for ice deposition was found to be 0.031 ± 0.001, while that for water evaporation was 0.054 ± 0.012. Results are considered in terms of the applicability of classical nucleation theory to the freezing of micrometre-sized droplets in cirrus clouds, with implications for the parameterization of homogeneous ice nucleation in numerical models.